Summer protocol - Matthew Partridge (458241) (2025)
A three‐panel lab scene showing one scientist struggling with equipment, another proposing a “summer‐proof” redesign, and a third suggesting simply putting down an ice cream. It pokes fun at lab work in hot weather.